EDUKASI SEKSUALITAS BAGI REMAJA - Lukas, Jesica; Namangge, Lini; Makalikis, Kezya; Ilat, Irene (PT. Giat Konseling Nusantara, 2024)
Sex education should be provided from a young age, as a preparation for changes in oneself and the environment. Sex education for adolescents is crucial for understanding sexual information, having awareness of the importance of understanding sexual issues, understanding the functions of sexuality, and addressing sexual issues for adolescents. Sex education for adolescents also helps prevent sexual problems, such as premarital sex or sex outside of marriage, which can lead to negative effects such as poor health, reduced reproductive health, and the risk of sexually transmitted diseases. Sex education for adolescents also directs adolescents towards low levels of knowledge about reproductive health, particularly in terms of protecting oneself from reproductive health risks. The level of knowledge among Indonesian adolescents about reproductive health is low, particularly in terms of protecting oneself from reproductive health risks. Sex education for adolescents is necessary to prevent confusion during the transition from childhood to adulthood. Sex education for adolescents is also necessary to protect reproductive organs on their bodies and prevent others from touching their reproductive organs, especially for adolescent girls. In this article, we will discuss the importance of sex education for adolescents, the factors that influence sex education among adolescents, and the effects that adolescents experience when engaging in premarital sex or sex outside of marriage.